A Game Theoretical Frawework For Multimedia Learning - Ang, Chee Siang (2004)
This thesis examines game theories for computer games and proposes game theories as a framework for designing multimedia learning. The analysis focuses on two major theories: ludology and narratology. Ludology is the study of computer games as play and game activities, while narratology is the study of computer games as stories.